2016
DOI: 10.1007/s11947-016-1713-2
|View full text |Cite
|
Sign up to set email alerts
|

Overall and Local Bread Expansion, Mechanical Properties, and Molecular Structure During Bread Baking: Effect of Emulsifying Starches

Abstract: In order to determine the relationship between molecular structure of wheat bread dough, its mechanical properties, total and local bread expansion during baking and final bread quality, different methods (rheological, nuclear magnetic resonance, magnetic resonance imaging and general bread characterisation) were employed. The study was extended on wheat dough with starch modified by octenyl succinic anhydride (OSA) in order to generalise the results. The interest of investigating multi-scale changes occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…In addition, Dapčević-Hadnađev et al [ 11 ] observed that the pregelatinized preparation causes an increase in the water absorption of gluten-free dough based on rice starch with added hemp protein. According to Pojić et al [ 16 ], the OSA starch absorbs water to a greater extent below the pasting temperature improving the dough yield, while at the same time making it more resistant to deformation during the first phase of baking, which can be explained by strengthening of walls surrounding gas bubbles in the dough. On the other hand, volume reduction occurs to a lesser extent during the second baking phase due to the higher stiffness of the dough.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dapčević-Hadnađev et al [ 11 ] observed that the pregelatinized preparation causes an increase in the water absorption of gluten-free dough based on rice starch with added hemp protein. According to Pojić et al [ 16 ], the OSA starch absorbs water to a greater extent below the pasting temperature improving the dough yield, while at the same time making it more resistant to deformation during the first phase of baking, which can be explained by strengthening of walls surrounding gas bubbles in the dough. On the other hand, volume reduction occurs to a lesser extent during the second baking phase due to the higher stiffness of the dough.…”
Section: Resultsmentioning
confidence: 99%
“…Dapčević-Hadnađev et al [ 15 ] observed that the introduction of OSA starch may result in a decreased stability of wheat dough, but it improves bread volume and texture. Pojić et al [ 16 ] observed that OSA starch absorbs more water and, in this way, it increases dough yield. Akram et al [ 17 ] stated that OSA starch causes an increase in the viscosity of wheat flour dispersion during pasting.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent decrease of the | G *| and tan δ might have been ascribed to the starch granular structure starts to disintegrate and the crystalline structure melts . The higher | G *| max of the WS– and CS–gluten doughs compared to the TS–, PS–, and SS–gluten doughs indicates a greater degree of structural hardening, contributing to the prevention of dough shrinkage caused by oven‐spring during heating . This might have been ascribed to the higher amylose content in WS and CS.…”
Section: Resultsmentioning
confidence: 99%
“…Production of staple foods such as steamed and baked breads is a process of dough processing, which could be divided into three main stages: mixing, fermentation, and thermal setting (i.e., baking/steaming) . As the connection between mixing and thermal setting, the fermentation of the dough includes yeast utilizing substrates and producing gas (mainly carbon dioxide or CO 2 ) into the dough .…”
Section: Introductionmentioning
confidence: 99%
“…Emulsifier might create a thin layer which can entrap carbon dioxide and strengthen the dough, thus the bread has a strong ability to expand [26]. Hydrocolloid is also has the similar function for improving baking expansion due to its role as a gluten substitute.…”
Section: Fig 1 Correlation Between Overall Parameter To Baking Expanmentioning
confidence: 99%